NAVIGATING UNCERTAINTY: THE ROLE OF FINANCIAL ACCESS IN POVERTY ALLEVIATION DURING ECONOMIC CRISES - Askar, Media Wahyudi (Jurnal Kebijakan Pemerintahan, 2024)
Abstract Access to financial services has long been recognized as a vital tool in poverty alleviation and economic development. Using logistic regression analysis, the study investigates the impact of financial access, particularly access to loans, on various poverty indicators, with a focus on gender dynamics and urban-rural disparities during economic crises. The analysis reveals that access to loans significantly influences key poverty indicators, including personal income increase, obtaining loans for business ventures, and opening new businesses. While the overall impact is positive, gender-specific differences in the significance of financial access indicate the need for tailored approaches. Women entrepreneurs, in particular, benefit significantly from access to loans, highlighting the importance of customized financial inclusion programs. Furthermore, the study finds that the impact of access to loans varies between urban and rural settings, with loans playing a more critical role in stimulating entrepreneurship and economic activity in rural areas. Policy implications from the analysis emphasize inclusive financial programs for both genders and addressing urban-rural gaps. Prioritizing initiatives to enhance women's credit access and rural entrepreneurship can unlock economic potential and promote inclusive growth. Keywords: financial access, poverty, economic crises